# Improper Integrals

## Solved Problems

Click or tap a problem to see the solution.

### Example 7

Calculate the integral $\int\limits_{ - \infty }^{ - 1} {\frac{{dx}}{{{x^2} + 4x + 5}}}.$

### Example 8

Calculate the integral $\int\limits_1^\infty {\frac{{dx}}{{{x^2} - 6x + 13}}}.$

### Example 9

Determine whether the improper integral ${\int\limits_{ - \infty }^\infty} {\frac{{dx}}{{{x^2} + 2x + 8}}}$ converges or diverges?

### Example 10

Determine whether the integral $\int\limits_0^\infty {\frac{{dx}}{{{x^2} + 2x + 2}}}$ converges or diverges?

### Example 11

Determine whether the integral ${\int\limits_1^\infty} {{\frac{{\sin x}}{{\sqrt {{x^3}} }}} dx}$ converges or diverges?

### Example 12

Determine whether the integral ${\int\limits_0^4} {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}}$ converges or diverges?

### Example 13

Determine for what values of $$k$$ the integral ${\int\limits_0^1} {\frac{{dx}}{{{x^k}}}}\;\left( {k \gt 0,k \ne 1} \right)$ converges?

### Example 14

Find the area above the curve $y = \ln x$ in the lower half-plane between $$x = 0$$ and $$x = 1.$$

### Example 15

Find the circumference of the unit circle.

### Example 7.

Calculate the integral $\int\limits_{ - \infty }^{ - 1} {\frac{{dx}}{{{x^2} + 4x + 5}}}.$

Solution.

We complete the square in the denominator:

${x^2} + 4x + 5 = \left( {{x^2} + 4x + 4} \right) + 1 = {\left( {x + 2} \right)^2} + 1.$

Then

$\int\limits_{ - \infty }^{ - 1} {\frac{{dx}}{{{x^2} + 4x + 5}}} = \int\limits_{ - \infty }^{ - 1} {\frac{{dx}}{{{{\left( {x + 2} \right)}^2} + 1}}} = \lim\limits_{n \to - \infty } \int\limits_n^{ - 1} {\frac{{dx}}{{{{\left( {x + 2} \right)}^2} + 1}}} = \lim\limits_{n \to - \infty } \left[ {\arctan \left( {x + 2} \right)} \right]_n^{ - 1} = \lim\limits_{n \to - \infty } \left[ {\arctan 1 - \arctan \left( {n + 2} \right)} \right] = \frac{\pi }{4} - \left( { - \frac{\pi }{2}} \right) = \frac{{3\pi }}{4}.$

Hence, the integral converges.

### Example 8.

Calculate the integral $\int\limits_1^\infty {\frac{{dx}}{{{x^2} - 6x + 13}}}.$

Solution.

First we complete the square in the denominator:

${x^2} - 6x + 13 = \left( {{x^2} - 6x + 9} \right) + 4 = {\left( {x - 3} \right)^2} + {2^2}.$

Taking the limit, we obtain:

$\int\limits_1^\infty {\frac{{dx}}{{{x^2} - 6x + 13}}} = \int\limits_1^\infty {\frac{{dx}}{{{{\left( {x - 3} \right)}^2} + {2^2}}}} = \lim\limits_{n \to \infty } \int\limits_1^n {\frac{{dx}}{{{{\left( {x - 3} \right)}^2} + {2^2}}}} = \lim\limits_{n \to \infty } \left[ {\frac{1}{2}\arctan \frac{{x - 3}}{2}} \right]_1^n = \frac{1}{2}\lim\limits_{n \to \infty } \Bigl[ {\arctan \frac{{n - 3}}{2} - \arctan \left( { - 1} \right)} \Bigr] = \frac{1}{2}\left( {\frac{\pi }{2} - \left( { - \frac{\pi }{4}} \right)} \right) = \frac{1}{2} \cdot \frac{{3\pi }}{4} = \frac{{3\pi }}{8}.$

The integral converges.

### Example 9.

Determine whether the improper integral ${\int\limits_{ - \infty }^\infty} {\frac{{dx}}{{{x^2} + 2x + 8}}}$ converges or diverges?

Solution.

We can write this integral as

$I = \int\limits_{ - \infty }^\infty {\frac{{dx}}{{{x^2} + 2x + 8}}} = \int\limits_{ - \infty }^0 {\frac{{dx}}{{{x^2} + 2x + 8}}} + \int\limits_0^\infty {\frac{{dx}}{{{x^2} + 2x + 8}}} .$

By the definition of an improper integral, we have

$I = \int\limits_{ - \infty }^\infty {\frac{{dx}}{{{x^2} + 2x + 8}}} = \int\limits_{ - \infty }^0 {\frac{{dx}}{{{x^2} + 2x + 8}}} + \int\limits_0^\infty {\frac{{dx}}{{{x^2} + 2x + 8}}} = \lim\limits_{M \to - \infty } \int\limits_M^0 {\frac{{dx}}{{{x^2} + 2x + 8}}} + \lim\limits_{N \to \infty } \int\limits_0^N {\frac{{dx}}{{{x^2} + 2x + 8}}} = \lim\limits_{M \to - \infty } \int\limits_M^0 {\frac{{dx}}{{{{\left( {x + 1} \right)}^2} + 7}}} + \lim\limits_{N \to \infty } \int\limits_0^N {\frac{{dx}}{{{{\left( {x + 1} \right)}^2} + 7}}} = \lim\limits_{M \to - \infty } \left. {\left( {\frac{1}{{\sqrt 7 }}\arctan \frac{{x + 1}}{{\sqrt 7 }}} \right)} \right|_M^0 + \lim\limits_{N \to \infty } \left. {\left( {\frac{1}{{\sqrt 7 }}\arctan \frac{{x + 1}}{{\sqrt 7 }}} \right)} \right|_0^N = \frac{1}{{\sqrt 7 }}\left( {\arctan \frac{1}{{\sqrt 7 }} - \lim\limits_{M \to - \infty } \arctan \frac{{M + 1}}{{\sqrt 7 }}} \right) + \frac{1}{{\sqrt 7 }}\left( {\lim\limits_{N \to \infty } \arctan \frac{{N + 1}}{{\sqrt 7 }} - \arctan \frac{1}{{\sqrt 7 }}} \right) = \cancel{\frac{1}{{\sqrt 7 }}\arctan \frac{1}{{\sqrt 7 }}} - \frac{1}{{\sqrt 7 }} \cdot \left( { - \frac{\pi }{2}} \right) + \frac{1}{{\sqrt 7 }} \cdot \frac{\pi }{2} - \cancel{\frac{1}{{\sqrt 7 }}\arctan \frac{1}{{\sqrt 7 }}} = \frac{1}{{\sqrt 7 }} \cdot \frac{\pi }{2} + \frac{1}{{\sqrt 7 }} \cdot \frac{\pi }{2} = \frac{\pi }{{\sqrt 7 }}.$

As both the limits exist and are finite, the given integral converges.

### Example 10.

Determine whether the integral $\int\limits_0^\infty {\frac{{dx}}{{{x^2} + 2x + 2}}}$ converges or diverges?

Solution.

This improper integral has an infinite upper limit of integration. Hence, by definition,

$\int\limits_0^\infty {\frac{{dx}}{{{x^2} + 2x + 2}}} = \lim\limits_{n \to \infty } \int\limits_0^n {\frac{{dx}}{{{x^2} + 2x + 2}}} = \lim\limits_{n \to \infty } \int\limits_0^n {\frac{{dx}}{{{{\left( {x + 1} \right)}^2} + 1}}} = \lim\limits_{n \to \infty } \left. {\arctan \left( {x + 1} \right)} \right|_0^n = \lim\limits_{n \to \infty } \left[ {\arctan \left( {n + 1} \right) - \arctan 1} \right] = \frac{\pi }{2} - \frac{\pi }{4} = \frac{\pi }{4}.$

The integral converges and is equal to $$\frac{\pi }{4}.$$

### Example 11.

Determine whether the integral ${\int\limits_1^\infty} {{\frac{{\sin x}}{{\sqrt {{x^3}} }}} dx}$ converges or diverges?

Solution.

We can write the obvious inequality for the absolute values:

$\left| {\frac{{\sin x}}{{\sqrt {{x^3}} }}} \right| \le \left| {\frac{1}{{\sqrt {{x^3}} }}} \right| = \left| {\frac{1}{{{x^{\frac{3}{2}}}}}} \right|.$

It's easy to show that the integral $${\int\limits_1^\infty} {\left| {\frac{1}{{\sqrt {{x^3}} }}} \right|dx}$$ converges (see also Example 1.) Indeed

$\int\limits_1^\infty {\left| {\frac{1}{{\sqrt {{x^3}} }}} \right|dx} = \int\limits_1^\infty {\frac{{dx}}{{\sqrt {{x^3}} }}} = \int\limits_1^\infty {\frac{{dx}}{{{x^{\frac{3}{2}}}}}} = \int\limits_1^\infty {{x^{ - \frac{3}{2}}}dx} = \lim\limits_{n \to \infty } \int\limits_1^n {{x^{ - \frac{3}{2}}}dx} = \lim\limits_{n \to \infty } \left. {\left( {\frac{{{x^{ - \frac{3}{2} + 1}}}}{{ - \frac{3}{2} + 1}}} \right)} \right|_1^n = - 2\lim\limits_{n \to \infty } \left. {\left( {\frac{1}{{\sqrt x }}} \right)} \right|_1^n = - 2\lim\limits_{n \to \infty } \left( {\frac{1}{{\sqrt n }} - 1} \right) = - 2\left( {0 - 1} \right) = 2.$

Then we conclude that the integral $${\int\limits_1^\infty} {\left| {\frac{{\sin x}}{{\sqrt {{x^3}} }}} \right|dx}$$ also converges by Comparison Test $$1.$$ Hence, the given integral $${\int\limits_1^\infty} {{\frac{{\sin x}}{{\sqrt {{x^3}} }}} dx}$$ converges (absolutely) by Comparison Test $$3.$$

### Example 12.

Determine whether the integral ${\int\limits_0^4} {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}}$ converges or diverges?

Solution.

There is a discontinuity in the integrand at $$x = 2,$$ so that we must consider two improper integrals:

$\int\limits_0^4 {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} = \int\limits_0^2 {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} + \int\limits_2^4 {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} .$

Using the definition of an improper integral, we obtain

$\int\limits_0^2 {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} + \int\limits_2^4 {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} = \lim\limits_{\tau \to 0 + } \int\limits_0^{2 - \tau } {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} + \lim\limits_{\tau \to 0 + } \int\limits_{2 + \tau }^4 {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} .$

For the first integral,

$\lim\limits_{\tau \to 0 + } \int\limits_0^{2 - \tau } {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}} = \lim\limits_{\tau \to 0 + } \int\limits_0^{2 - \tau } {{{\left( {x - 2} \right)}^{ - 3}}d\left( {x - 2} \right)} = \lim\limits_{\tau \to 0 + } \left[ {\frac{{{{\left( {x - 2} \right)}^{ - 3 + 1}}}}{{ - 3 + 1}}} \right]_0^{2 - \tau } = - \frac{1}{2}\lim\limits_{\tau \to 0 + } \left. {\left[ {\frac{1}{{{{\left( {x - 2} \right)}^2}}}} \right]} \right|_0^{2 - \tau } = - \frac{1}{2}\lim\limits_{\tau \to 0 + } \left[ {\frac{1}{{{{\left( {2 - \tau - 2} \right)}^2}}} - \frac{1}{{{{\left( {0 - 2} \right)}^2}}}} \right] = - \frac{1}{2}\lim\limits_{\tau \to 0 + } \left( {\frac{1}{{{\tau ^2}}} - \frac{1}{4}} \right) = - \infty .$

As it is divergent, the given integral $${\int\limits_0^4} {\frac{{dx}}{{{{\left( {x - 2} \right)}^3}}}}$$ is also divergent.

### Example 13.

Determine for what values of $$k$$ the integral ${\int\limits_0^1} {\frac{{dx}}{{{x^k}}}}\;\left( {k \gt 0,k \ne 1} \right)$ converges?

Solution.

The integrand has discontinuity at the point $$x = 0,$$ so that we can write the integral as

$\int\limits_0^1 {\frac{{dx}}{{{x^k}}}} = \lim\limits_{\tau \to 0 + } \int\limits_\tau ^1 {\frac{{dx}}{{{x^k}}}} = \lim\limits_{\tau \to 0 + } \int\limits_\tau ^1 {{x^{ - k}}dx} = \lim\limits_{\tau \to 0 + } \left. {\left( {\frac{{{x^{ - k + 1}}}}{{ - k + 1}}} \right)} \right|_\tau ^1 = \frac{1}{{1 - k}} \cdot \lim\limits_{\tau \to 0 + } \left. {\left( {{x^{ - k + 1}}} \right)} \right|_\tau ^1 = \frac{1}{{1 - k}} \cdot \lim\limits_{\tau \to 0 + } \left( {{1^{ - k + 1}} - {\tau ^{ - k + 1}}} \right) = \frac{1}{{1 - k}} \lim\limits_{\tau \to 0 + } \left( {1 - {\tau ^{1 - k}}} \right).$

As you can see from this expression, there are $$2$$ cases:

• If $$0 \lt k \lt 1,$$ then
$\lim\limits_{\tau \to 0 +} {\tau ^{1 - k}} = 0$

and the integral converges;

• If $$k \gt 1,$$ then
$\lim\limits_{\tau \to 0 +} {\tau ^{1 - k}} = \lim\limits_{\tau \to 0 +} {\frac{1}{{{\tau ^{k - 1}}}}} = \infty$

and the integral diverges.

### Example 14.

Find the area above the curve $y = \ln x$ in the lower half-plane between $$x = 0$$ and $$x = 1.$$

Solution.

The given region is sketched in Figure $$7.$$

Since it is infinite, we calculate the improper integral to find the area:

$\int\limits_0^1 {\ln xdx} = \lim\limits_{\tau \to 0 + } \int\limits_\tau ^1 {\ln xdx} .$

Use integration by parts. Let $$u = \ln x,$$ $$dv = dx.$$ Then $$du = {\frac{{dx}}{x}},$$ $$v = x.$$

Thus

$\lim\limits_{\tau \to 0 + } \int\limits_\tau ^1 {\ln xdx} = \lim\limits_{\tau \to 0 + } \left[ {\left. {\left( {x\ln x} \right)} \right|_\tau ^1 - \int\limits_\tau ^1 {x\frac{{dx}}{x}} } \right] = \lim\limits_{\tau \to 0 + } \left. {\left[ {x\ln x - x} \right]} \right|_\tau ^1 = \lim\limits_{\tau \to 0 + } \left[ {\left( {\ln 1 - 1} \right) - \left( {\tau \ln \tau - \tau } \right)} \right] = \left( {0 - 1} \right) - \lim\limits_{\tau \to 0 + } \left[ {\tau \left( {\ln \tau - 1} \right)} \right] = - 1 - \lim\limits_{\tau \to 0 + } \frac{{\ln \tau - 1}}{{\frac{1}{\tau }}}.$

We can apply L'Hopital's rule to find the limit:

$\lim\limits_{\tau \to 0 + } \frac{{\ln \tau - 1}}{{\frac{1}{\tau }}} = \lim\limits_{\tau \to 0 + } \frac{{\frac{1}{\tau }}}{{ - \frac{1}{{{\tau ^2}}}}} = - \lim\limits_{\tau \to 0 + } \frac{{{\tau ^2}}}{\tau } = - \lim\limits_{\tau \to 0 + } \tau = 0.$

Hence, the improper integral is

$\lim\limits_{\tau \to 0 + } \int\limits_\tau ^1 {\ln xdx} = - 1 - \lim\limits_{\tau \to 0 + } \frac{{\ln \tau - 1}}{{\frac{1}{\tau }}} = - 1 - 0 = - 1.$

As you can see from the figure above, the required area is

$S = \left| {\lim\limits_{\tau \to 0 + } \int\limits_\tau ^1 {\ln xdx} } \right| = 1.$

### Example 15.

Find the circumference of the unit circle.

Solution.

We calculate the length of the arc of the circle in the first quadrant between $$x = 0$$ and $$x = 1$$ and then multiply the result by $$4.$$

The equation of the circle centered at the origin is

${x^2} + {y^2} = 1.$

Then the arc of the circle in the first quadrant (Figure $$8$$) is described by the function

$y = \sqrt {1 - {x^2}} ,\;\;\; 0 \le x \le 1.$

Find the derivative of the function:

$y' = \frac{d}{{dx}}\sqrt {1 - {x^2}} = \frac{{ - \cancel{2}x}}{{\cancel{2}\sqrt {1 - {x^2}} }} = \frac{{ - x}}{{\sqrt {1 - {x^2}} }}.$

Since the length of an arc is given by $$\int\limits_{x = \alpha }^{x = \beta } {\sqrt {1 + {{\left( {y'} \right)}^2}} dx},$$ we obtain

$\int\limits_0^1 {\sqrt {1 + {{\left( {\frac{{ - x}}{{\sqrt {1 - {x^2}} }}} \right)}^2}} dx} = \int\limits_0^1 {\sqrt {1 + \frac{{{x^2}}}{{1 - {x^2}}}} dx} = \int\limits_0^1 {\sqrt {\frac{{1 - \cancel{x^2} + \cancel{x^2}}}{{1 - {x^2}}}} dx} = \int\limits_0^1 {\frac{{dx}}{{\sqrt {1 - {x^2}} }}} .$

Now we calculate the improper integral $$\int\limits_0^1 {\frac{{dx}}{{\sqrt {1 - {x^2}} }}}:$$

$\int\limits_0^1 {\frac{{dx}}{{\sqrt {1 - {x^2}} }}} = \lim\limits_{\tau \to 0 + } \int\limits_0^{1 - \tau } {\frac{{dx}}{{\sqrt {1 - {x^2}} }}} = \lim\limits_{\tau \to 0 + } \left. {\left( {\arcsin x} \right)} \right|_0^{1 - \tau } = \lim\limits_{\tau \to 0 + } \left[ {\arcsin \left( {1 - \tau } \right) - \arcsin 0} \right] = \arcsin 1 - 0 = \frac{\pi }{2}.$

Thus, the circumference of the unit circle is $$\frac{\pi }{2} \cdot 4 = 2\pi .$$